Formulation of a Synergistic Herbal Blend of Green Tea (Camelia sinensis) and Traditional Spices for Immune Support and Anxiety Relief - Ananta Ardyansyah; Dika Putra Wijaya; Danar Danar; Tsalis Jauza Nareswari; Anggun Frista Utami; Annisaa Annisaa; Diana Nadhifah; Lely Fitrianingrum (Biology, Medicine, & Natural Product Chemistry, 2025)
COVID-19 not only brings problems to physical health but also mental health, such as anxiety. Excessive anxiety is very dangerous because it can reduce the number of white blood cells in the bloodstream. Excessive anxiety also triggers the production of excess cortisol which interferes with the immune system. This could be overcome by the combination of tea which has a relaxing effect with several immunomodulatory herbs. Green tea (Camellia sinensis) has been shown to have the effect of reducing one's anxiety and improving one's psychological health. The tea is combined with other spices, namely (Zingiber officinale), turmeric (Curcuma domestica Val), and cinnamon (Cinnamomum burmannii). This study was conducted to find out that the combination formed has met safety standards, so it can be used as an immunity-boosting drink during a pandemic. Standardization includes testing for moisture content, ash content, and organoleptic tests. The results obtained were the water content of herbal tea was as much as 6.26%, while the ash content of the tea was 5.74%. The water content and ash content had met the standards of the Ministry of Health regarding the preparation of herbal medicines. The organoleptic test performed showed that the formulation obtained was dominated by the taste of ginger, the color of turmeric, and the smell of cinnamon.